(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the integration of Circular Economy (CE) principles within the Sustainable Supply Chain (SSC) framework through a cross-sectional approach.narrative integrative reviewThe study results show that theoretical models in the CE–SSC literature are still fragmented, with the dominance of NRBV, Industrial Ecology, and institutional theory approaches that have not been able to comprehensively integrate all circular loops. In addition, digital enablers such as IoT, AI, and blockchain have not been systematically integrated in existing models, creating important conceptual gaps in supporting traceability, coordination, and performance measurement of circular supply chains. This study offers an integrative framework that unites circular design, digital technology, supply chain coordination, reverse flow mechanisms, and sustainability outcomes. These findings provide academic contributions through comprehensive theoretical mapping and practical contributions in the form of guidance for organizations and policymakers in developing more effective, collaborative, and technology-based CE–SSC implementations.